2011
DOI: 10.1021/nl200604g
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Inhomogeneous Segregation in Graphene Growth on Epitaxial Metal Films

Abstract: Large-scale uniform graphene growth was achieved by suppressing inhomogeneous carbon segregation using a single domain Ru film epitaxially grown on a sapphire substrate. An investigation of how the metal thickness affected growth and a comparative study on metals with different crystal structures have revealed that locally enhanced carbon segregation at stacking domain boundaries of metal is the origin of inhomogeneous graphene growth. Single domain Ru film has no stacking domain boundary, and the graphene gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 28 publications
1
44
0
1
Order By: Relevance
“…Recently, Ref. [251] reported growth on Ni, Co and Ru on sapphire. Through the suppression of grain boundaries, Ref.…”
Section: Growth On Metals By Precipitationmentioning
confidence: 99%
“…Recently, Ref. [251] reported growth on Ni, Co and Ru on sapphire. Through the suppression of grain boundaries, Ref.…”
Section: Growth On Metals By Precipitationmentioning
confidence: 99%
“…Especially, the interaction between the metal surface and graphene is widely studied focusing on commensurate orientational relationships (called an epitaxy) between graphene and the metal surface with close-packed facet such as fcc(1 1 1) and hcp(0 0 0 1) [3][4][5][6][7][8][9], although such epitaxy has been suggested for a long time in the field of surface science prior to the discovery of CNTs and graphene [10,11]. Recently, epitaxial growth of the graphene on the highly orientated metal surface via the CVD process becomes a reality [12][13][14][15][16][17][18][19] and the mechanism of epitaxial growth has been examined. For example, Li and co-workers [13] used the carbon isotope labelling to track carbon atoms during the graphene growth on Ni and Cu surface and proposed two formation paths for the graphene growth: carbon diffusion, segregation and precipitation for the Ni (high carbon solubility metal) and surface adsorption and edge growth on the Cu (low carbon solubility metal).…”
Section: Introductionmentioning
confidence: 99%
“…This result was further supported by Bae et al [51] who showed it is Graphene-metal separation (nm) [43] Lattice mismatch (%) [44] Co ( possible to prepare large-area, monolayer graphene via roll-to-roll processes and found that the graphene domain sizes correspond to the size of the grain boundaries. Notably, several other studies have shown the synthesis of single-crystal graphene on noble metals such as Pt and Ru [52,53]. Figure 3 shows a schematic diagram representing the growth mechanism on single-crystalline and polycrystalline Ni substrates.…”
Section: Crystallinity and Morphology Of The Substrates Crystallinitymentioning
confidence: 99%